The Surface Structure and Thermal Properties of Novel Polymer Composite Films Based on Partially Phosphorylated Poly(vinyl alcohol) with Aluminum Phosphate - Asmalina Mohamed Saat; Mohd Rafie Johan (The Scientific World Journal)
Partially phosphorylated polyvinyl alcohol (PPVA) with aluminum phosphate (ALPO4) composites was synthesized by solution casting technique to produce (PPVA)100-y-(ALPO4)y (y = 0, 1, and 2). The surface structure and thermal properties of the films were characterized using Fourier transform infrared (FTIR) spectroscopy and thermogravimetric analysis (TGA). The results showed that the films have higher thermal stability with strong bonding between PPVA and ALPO4.